2002
DOI: 10.1046/j.1440-1827.2002.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of c‐erbB‐2 (HER‐2/neu) amplification in breast carcinoma by fluorescence in situ hybridization on tissue sections and imprinted cells

Abstract: Abnormalities in c-erbB-2 have attracted a great deal of attention. Treatment using an antibody against the c-erbB-2 gene product is effective against breast cancers with amplification and/or overexpression of c-erbB-2. There is an urgent need to establish methodology for selecting patients who would benefit from this therapy. A total of 235 breast carcinomas were examined for c-erbB-2 protein overexpression by immunohistochemistry. Tissue sections with discernible immunostaining from 52 tumors, 70 negative tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…3,6 FISH on cytologic specimens, including smears, fine needle aspirates, cytospins and imprint preparations, allows a rapid and reproducible quantitative analysis of DNA alterations in single cells, thus avoiding many of the drawbacks of tissue sections. 4,7,8 To our knowledge, only a small number of destained smears were included in studies that evaluated HER-2/neu by FISH on cytology. 5 In this study HER-2/neu was assessed in 69 archival MGG-stained cytologic specimens, including fine needle aspiration smears and cytospins obtained from primary and metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 FISH on cytologic specimens, including smears, fine needle aspirates, cytospins and imprint preparations, allows a rapid and reproducible quantitative analysis of DNA alterations in single cells, thus avoiding many of the drawbacks of tissue sections. 4,7,8 To our knowledge, only a small number of destained smears were included in studies that evaluated HER-2/neu by FISH on cytology. 5 In this study HER-2/neu was assessed in 69 archival MGG-stained cytologic specimens, including fine needle aspiration smears and cytospins obtained from primary and metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…13 Other studies in the United States also demonstrated greater sensitivity with FISH than with the BTA Stat test 14 and greater sensitivity than with cytology itself. 15 However, in Japan, the expense of FISH makes it unlikely that this approach will be adopted for general use; therefore, we must concentrate attention on those areas where it might have the most impact. In our series, while there were five cases each that were cytology-negative but positive for abnormality of chromosome 9 or 17, only one of these was positive for polysomy of both chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, fluorescence in situ hybridization (FISH) has been employed to detect chromosomal abnormalities in various malignant tumors, and it has proven to be very useful. [15][16][17] In the urological field, FISH has been used not only with paraffin-embedded solid tissue, but also with voided urine samples. [18][19][20][21] These latter can be readily collected from patients without the pain and psychological trauma associated with cystoscopy, with or without biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The specificities and sensitivities of the antibodies against HER-2 and EGFR were verified previously. [4][5][6][7]11,12 For EGFR detection, a high-temperature antigen unmasking technique was used: that is, autoclave the section in 0.01 M citrate buffer (pH 7.0) at 1211C for 10 min. Antibodies were visualized by avidin-biotin binding to peroxidase-conjugated HER-2 and EGFR positivity in the IHC analyses were reviewed by three pathologists (TT, SS, AO), who were unaware of the gene amplification.…”
Section: Ihcmentioning
confidence: 99%
“…This monoclonal antibodybased therapy has been approved for use in breast cancer patients and has demonstrated an ability to extend median survival time in metastatic breast cancer patients exhibiting HER-2 overexpression. 2 Similarly, IMC-C225 (cetuximab or Erbitux TM , ImClone Systems Inc., Branchburg, NJ, USA), a monoclonal antibody targeting EGFR, and among the various small molecule inhibitors of tyrosine kinases ZD1839 (gefitinib, Iressa TM , AstraZeneca, Macclesfield, UK) are now approved for use in patients with colorectal cancers (FDA News, February 12,2004) and non-small cell lung cancer, 3 respectively.…”
mentioning
confidence: 99%